2020
DOI: 10.1002/tcr.202000151
|View full text |Cite
|
Sign up to set email alerts
|

Triazolization of Enolizable Ketones with Primary Amines: A General Strategy toward Multifunctional 1,2,3‐Triazoles

Abstract: The development of metal‐free syntheses toward 1,2,3‐triazoles has been a burgeoning research area throughout the past decade. Despite the numerous advances, the scarceness of methods for the preparation of 1,5‐disubstituted 1,2,3‐triazoles from readily available substrates remained a challenge that was addressed by our group in 2016. A metal‐free three‐component reaction, which we have dubbed the triazolization reaction, was established for the rapid synthesis of 1,5‐disubstituted, fully functionalized and NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
0
12
0
2
Order By: Relevance
“…Very recently, our group reported the synthesis and spectroscopic properties of novel 1,2,3-triazole BOPAHY dyes and their corresponding triazolium salts ( Scheme 30 ) [ 84 ]. Thus, we started from N -tosyl-4,5,6,7-tetrahydroindol-4-one 118 and performed our in-house developed general metal-free triazolization reaction [ 85 , 86 , 87 , 88 , 89 ]. This route toward 1,2,3-triazoles starts from enolizable ketones, primary amines and 4-nitrophenyl azide as diazo-transfer agent.…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…Very recently, our group reported the synthesis and spectroscopic properties of novel 1,2,3-triazole BOPAHY dyes and their corresponding triazolium salts ( Scheme 30 ) [ 84 ]. Thus, we started from N -tosyl-4,5,6,7-tetrahydroindol-4-one 118 and performed our in-house developed general metal-free triazolization reaction [ 85 , 86 , 87 , 88 , 89 ]. This route toward 1,2,3-triazoles starts from enolizable ketones, primary amines and 4-nitrophenyl azide as diazo-transfer agent.…”
Section: Synthesis Of [45]-fused Polyheterocyclic Structuresmentioning
confidence: 99%
“…In 2016, our group reported a metal-free three-component reaction for the synthesis of 1,5-disubstituted 1,2,3-triazoles [ 20 , 21 , 22 ], known as the “triazolization reaction of ketones”. In 2020, it was shown by our laboratory that the acid-mediated denitrogenative ring opening of triazoloisoquinolines furnished various 1-methyleneisoquinolines [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a procedure was developed starting from FNPT 1a and primary amines that allowed for protein modification in excellent conversions without isolating the targeted aldehydes 7. Following our ongoing interest in the synthesis of 1,2,3-triazoles [36][37][38], we recognized the potential of this approach for the metal-free synthesis of 1-alkyl-4-formyl-As described by L'abbé, the equilibrium of the Cornforth rearrangement is shifted toward the triazole with the most electron-deficient substituent on the imine nitrogen. Fletcher et al, who further studied this rearrangement in 2018, observed the same trend [34].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a procedure was developed starting from FNPT 1a and primary amines that allowed for protein modification in excellent conversions without isolating the targeted aldehydes 7. Following our ongoing interest in the synthesis of 1,2,3-triazoles [36][37][38], we recognized the potential of this approach for the metal-free synthesis of 1-alkyl-4-formyl-1,2,3-triazoles 7. However, to the best of our knowledge, a metal-free and straightforward synthesis of FNPT 1a on a preparative scale was still lacking.…”
Section: Introductionmentioning
confidence: 99%